2017
DOI: 10.1021/acsenergylett.7b01057
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Solvent Coordination on Hybrid Organic–Inorganic Perovskite Formation

Abstract: Solution-processed hybrid organic−inorganic perovskites (HOIPs) from organoammonium halide and lead halide precursors form efficacious active layers for photovoltaics, light-emitting diodes, and flexible electronics. Though solvent−solute coordination plays a critical role in HOIP crystallization, the influence of solvent choice on such interactions is poorly understood. We demonstrate Gutmann's donor number, D N , as a parameter that indicates the coordinating ability of the processing solvent with the Pb 2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
429
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 322 publications
(475 citation statements)
references
References 42 publications
14
429
2
3
Order By: Relevance
“…FTIR shows both residual DMF and DMSO at characteristic stretching modes of υ C =O at ≈1660 cm −1 and υ S =O at ≈1000 cm −1 , respectively, in each antisolvent film . It has been previously shown that both DMF and DMSO form adducts with perovskite precursors, albeit with different strengths …”
Section: Resultsmentioning
confidence: 95%
“…FTIR shows both residual DMF and DMSO at characteristic stretching modes of υ C =O at ≈1660 cm −1 and υ S =O at ≈1000 cm −1 , respectively, in each antisolvent film . It has been previously shown that both DMF and DMSO form adducts with perovskite precursors, albeit with different strengths …”
Section: Resultsmentioning
confidence: 95%
“…The kinetics of film formation are counterintuitive from the perspective of solvent evaporation rates, as the boiling point/vapor pressure (20 °C) of GBL and DMSO are 204 °C/2.0 hPa and 189 °C/0.56 hPa, respectively, very much in favor of faster drying and solidification of the DMSO‐based ink as compared with GBL‐based one. Instead, the effective evaporation rate appears to be linked to other aspects of the solvent, such as the strength of complexation bonds between the solvents and Bi ions, which appears to be very much in favor of DMSO retention, just like the case of lead …”
Section: Resultsmentioning
confidence: 99%
“…Using these early studies as a guide and with the aid of in situ thickness, thermogravimetric, and Fourier transform IR spectroscopy (FTIR) measurements, we show that the solvent choice for MA 3 Bi 2 I 9 also plays a critical role. In particular, we show that DMSO solvent retention within MA 3 Bi 2 I 9 layers during processing is significantly higher compared with γ ‐butyrolactone (GBL), a behavior also noted in MAPbI 3 and linked to solvent‐metal interaction strengths . Use of DMSO:GBL solvent blends is then exploited to better control the crystallization and growth dynamics of the MA 3 Bi 2 I 9 layer, albeit with limited success.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Table 2 summarizes the health and safety and regulated and recommended industrial limits of these same chemicals. In addition, Moore et al [10] and Hamill et al [11] found that the lead center and solvent complexation to the lead center are important for proper phase formation and thin-film crystallization. Solubility of these components varies, with organic halides being more soluble and simpler to dissolve, while metal halides can be more challenging.…”
Section: Solution Processingmentioning
confidence: 99%